2010
DOI: 10.32398/cjhp.v8isi.2040
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a Pacific Islander Young Adult Perspective on Access to Higher Education

Abstract: The Pacific Islander (PI) community suffers disproportionately from illnesses and diseases, including diabetes, heart disease and cancer. While there are tremendous health needs within the PI community, there are few health care providers from the community that exist to help address these particular needs. Many efforts have focused on health care workforce diversity to reduce and eliminate health disparities, but few have examined the issues faced in the health care work force pipeline. Understanding educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For example, Native Hawaiians and other Pacific Islanders, who are often placed under the label “Asian,” face historical and social barriers that make accessing educational and professional opportunities difficult. 24 Furthermore, Southeast Asian Americans, such as Cambodian and Laotian Americans, have much lower household incomes and college education completion rates than many South and East Asian Americans. 23 AAMC data demonstrate that Southeast Asian Americans apply to medical school at a significantly lower rate than East and South Asian Americans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Native Hawaiians and other Pacific Islanders, who are often placed under the label “Asian,” face historical and social barriers that make accessing educational and professional opportunities difficult. 24 Furthermore, Southeast Asian Americans, such as Cambodian and Laotian Americans, have much lower household incomes and college education completion rates than many South and East Asian Americans. 23 AAMC data demonstrate that Southeast Asian Americans apply to medical school at a significantly lower rate than East and South Asian Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Of the research that exists regarding PI students in higher education, emerging themes concern limited socioeconomic opportunity for students and the need for greater institutional and social support and educational resources (Ah Sam & Robinson, 1998;Tran et al, 2010). PI students show strong extended family connections that can at times conflict with college obligations (Ah Sam & Robinson, 1998;Vakalahi, 2009, Tran et al, 2010.…”
Section: Pacific Islander Experiencesmentioning
confidence: 99%
“…Of the research that exists regarding PI students in higher education, emerging themes concern limited socioeconomic opportunity for students and the need for greater institutional and social support and educational resources (Ah Sam & Robinson, 1998;Tran et al, 2010). PI students show strong extended family connections that can at times conflict with college obligations (Ah Sam & Robinson, 1998;Vakalahi, 2009, Tran et al, 2010. Although much of the research is qualitative in nature, some quantitative research has suggested key variables such as culturally relevant pedagogy or college navigational skills are important for these students' success (Kana'iaupuni et al, 2011;Makuakane-Drechsel & Hagedorn, 2000;Panapasa et al, 2011;Sablan, 2015).…”
Section: Pacific Islander Experiencesmentioning
confidence: 99%
“…Diversifying the educational pipeline requires addressing the educational barriers that impact underrepresented and marginalized populations in higher education (5)(6)(7)(8). Integrative approaches include providing affordable college credits, and college preparation activities to high school students which help to demystify the college-going experience for underrepresented and marginalized students (5,9).…”
Section: Introductionmentioning
confidence: 99%